Neonatal Care Practices Among Ready Made Garments Working Mothers - Mazumder, Pranay Kumar; Sharma, Jhulan Das; Khan, Mohammad Asif (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Neonatal care is an essential care dependent on team work and plays a great role in children’s survival and development. Effective ante natal care, safe delivery and care in the first week of neonate baby are crucial for neonatal mortality and morbidity. The purpose of the study is to identify neonatal care practices and beliefs, their harmful and beneficial characteristics among the RMG working mothers of below five years children. Materials and methods: A descriptive type of cross sectional study was conducted on the knowledge on Neonatal care among the Ready Made Garments (RMG) working mothers. In this study a total of 120 mothers were selected by Global Specialist Garments limited-1 (GSGL-1) at Sadarghat, Chittagong from June to July, 2014. Data were collected by using structured questionnaire through face to face interview and were then compiled, processed and analyzed by SPSS-version 20. Results: The age range of the respondents was in between 18-39 years. In this study we found that 41.67% mothers had single child while about 10% mothers had 4 or more children. Among the mothers 80% had knowledge about benefits of breastfeeding and 78.33% had given colostrums to their babies. A total 55 mothers initiate breastfeeding within an hour and 91.67% heard about exclusive breastfeeding. About 66.67% respondents delivered the last child at home among them 75% conducted by untrained Dai. Only 58.33% had knowledge about proper care of the umbilical cord. Conclusion: In this study most of the mothers did not complete their secondary education and had a lack of knowledge on neonatal care practice. More over working mothers unable to give enough time for neonatal care. National policy and planning for maternity leave should be followed in our RMG factories to minimize the problem. JCMCTA 2018 ; 29 (1) : 42-46